A comparative study of high-altitude swimming training in China, Japan and America - Yu, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The United States has maintained a dominant status in competitive swimming for a number of years. This position may be related to their high-altitude swimming training methods. In recent years, Japanese swimmers have made remarkable improvements through high-altitude training and Chinese swimmers have recognized the importance of the type of training. A detailed comparative analysis was made regarding the purpose, model, cycle, and the strength of high-altitude swimming training in China, Japan and the United States. Methods A review of the literature was conducted followed by comparative analysis of the findings: Results / Discussion Comparison of the purpose of altitude training across the countries indicated that the Chinese groups aimed to improve endurance in winter training, whereas the major Japanese and American swimmers major goal was to improve performance before competition and also for day to day training in the US group. In terms of the nature of the training, groups from all 3 countries used natural hypoxic training supplemented by artificial hypoxic training. Differences were shown between the 3 groups with respect to the intensity and volume of the training carried out at high altitude. The Chinese swimmers were exposed to 3-4 weeks of training with training volume and intensity slightly lower than that used at sea level. In Japan and America swimmers were exposed to 3 - 4 weeks of training at high altitude with volume and intensity at a similar to that used at sea level. Japan and the United States have paid the greatest attention to high-altitude training, and have continued to explore options for new training methods. Training in China should focus on developing a new model of artificial hypoxic training, based on the experiences from Japan and America. Finally, it is necessary to understand the methods and basis of high-altitude training as well as taking an individualized approach to high-altitude training.